2017
DOI: 10.1038/srep46347
|View full text |Cite
|
Sign up to set email alerts
|

Glycoengineering of pertuzumab and its impact on the pharmacokinetic/pharmacodynamic properties

Abstract: Pertuzumab is an antihuman HER2 antibody developed for HER2 positive breast cancer. Glycosylation profiles are always the important issue for antibody based therapy. Previous findings have suggested the impact of glycosylation profiles on the function of antibodies, like pharmacodynamics, antibody-dependent cellular cytotoxicity (ADCC) and complement-dependent cytotoxicity (CDC). However, the roles of fucose and sialic acid in the function of therapeutic antibodies still need further investigation, especially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 50 publications
2
16
0
Order By: Relevance
“…The same enzymatic modification was applied in the ADCC assay to Pertuzumab, a therapeutic mAb, which recognizes human epidermal growth factor receptor 2 (HER2). A sixfold higher cytotoxic effect was observed in the case of sialylated and defucosylated Pertuzumab, and a 20-fold higher effect of cell lysis after desialylation and defucosylation of this mAb [34]. These results showed that the effect of IgG desialylation strictly depends on the presence of core fucose.…”
Section: Discussionmentioning
confidence: 61%
“…The same enzymatic modification was applied in the ADCC assay to Pertuzumab, a therapeutic mAb, which recognizes human epidermal growth factor receptor 2 (HER2). A sixfold higher cytotoxic effect was observed in the case of sialylated and defucosylated Pertuzumab, and a 20-fold higher effect of cell lysis after desialylation and defucosylation of this mAb [34]. These results showed that the effect of IgG desialylation strictly depends on the presence of core fucose.…”
Section: Discussionmentioning
confidence: 61%
“…Another important Fc-mediated immune effector function that plays the most important role in depleting tumor cells is called antibody-dependent cellular cytotoxicity (ADCC). It has been proved previously that the absence of core fucose on Fc N-glycan structures can lead to enhanced ADCC activity (23, 24). It has also been confirmed that apart from afucosylation, galactosylation levels could also influence ADCC activity; however, the role of afucosylation is more prominent.…”
Section: Resultsmentioning
confidence: 99%
“…For example, expression of exogenous sialidase A gene in mammalian cells resulted in the expression of a soluble enzyme that removed sialic acid from antibodies secreted into the medium. ADCC assay showed that the two IgG1 antibodies expressed in sialidase A‐transfected cells had greater than 10‐folds improved potency compared to the control mock‐transfected IgG1s (Naso et al, ).The removal of terminal sialylation also increased the ADCC activity of pertuzumab (Luo et al, ). Alternatively, several recent investigations indicated that Fc sialylation does not impact the in vitro FcγRI and FcγRIIIa receptor binding and ADCC activity of IgG1, whether it is mono‐ or di‐sialylated glycans (Quast et al, ; Thomann et al, ).…”
Section: Antibody Glycoengineering Strategiesmentioning
confidence: 99%
“…However, mono‐sialylated IgG1 showed a slight binding improvement to FcγRIIa than bi‐sialylated IgG1 (Boyd, Lines, & Patel, ; Thomann et al, ). Interestingly, the elimination of core fucosylation and its impact on FcγRIIIa binding affinity and ADCC activity is independent of terminal sialylation (Li et al ; Luo et al ). Regarding CDC activity, the presence of terminal sialic acid was found to lower IgG1 C1q binding and reduce C3b deposition on the cell surface (Quast et al, ).…”
Section: Antibody Glycoengineering Strategiesmentioning
confidence: 99%